Role of Efflux Pumps in Adaptation and Resistance of Listeria monocytogenes to Benzalkonium Chloride - Romanova, N. A. (American Society for Microbiology, 2006)
In this study, potential mechanisms underlying resistance and adaptation to benzalkonium chloride (BC) in Listeria monocytogenes were investigated. Two groups of strains were studied. The first group consisted of strains naturally sensitive to BC which could be adapted to BC. The second group consisted of naturally resistant strains. For all adapted isolates, there was a correlation between the resistance to BC and ethidium bromide, but this was not the case for the naturally resistant isolates. To investigate the role of efflux pumps in adaptation or resistance, reserpine, an efflux pump inhibitor, was added to the strains. Addition of reserpine to the sensitive and adapted strains resulted in a decrease in the MIC for BC, whereas no such decrease was observed for the resistant strains, indicating that efflux pumps played no role in the innate resistance of certain strains of L. monocytogenes to this compound. Two efflux pumps (MdrL and Lde) have been described in L. monocytogenes. Studies showed low and intermediate levels of expression of the genes encoding the efflux pumps for two selected resistant strains, H7764 and H7962, respectively. Adaptation to BC of sensitive isolates of L. monocytogenes resulted in significant increases in expression of mdrl (P < 0.05), but no such increase was observed for lde for two adapted strains of L. monocytogenes, LJH 381 (P = 0.91) and C719 (P = 0.11). This indicates that the efflux pump Mdrl is at least partly responsible for the adaptation to BC.